A Pneumococcal Septic Arthritis in a Patient with Multiple Myeloma - Yakupoğulları, Yusuf; Karakurt, Lokman; Dilek, Aziz Ramazan; Kizirgil, Ahmet (Fırat University, 2007)
In this case report, a case of septic arthritis caused by Streptococcus pneumoniae from an old patient with multiple myeloma was presented, who received therapy due to vertebral fracture in the orthopedics clinic of our institute. The patient fully recovered without any complication, following the cefamezin infusion for four weeks. S. pneumoniae should be regarded as an aetiologic agent particularly among children and high risk bearing old patients. ©2007, Firat University, Medical Faculty

Bu olgu bildirisinde, hastanemiz ortopedi kliniğinde vertebral fraktür nedeniyle yatarak tedavi görmekte olan multiple myelomalı yaşlı bir hastada gelişen, Streptococcus pneumoniae'nın neden olduğu bir septik artrit olgusu sunulmuştur. Hasta, dört haftalık sefamezin tedavisini takiben komplikasyonsuz olarak tamamen iyileşmiştir. S. pneumoniae'nın özellikle çocuklar veya riskli yaşlı hastalarda nadiren de olsa septik artrit olgularına yol açabileceği göz önünde tutulmalıdır. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Multiple Myelomalı Hastada Gelişen Bir Pnömokok Septik Artriti